PENINGKATAN KEMAMPUAN MEMBACA AL QUR’AN MELALUI PENGENALAN MAKHORIJUL HURUF PADA ANAK MENGGUNAKAN METODE SOROGAN - Muchamad Nasir (JIP: Jurnal Ilmu Pendidikan, 2023)
This research focuses on how to apply Sorogan Method in reading makharijul letters and whether there is an increase the ability to read makharijul letters after using the sorogan method. The research used PAR (Participatory Action Research) approach. The results of this study are the use of the sorogan method carried out in groups and students have increased the ability to read the Qur'an through the introduction of makhorijul letters through the sorogan method. This research has an impact on improving the ability of students in reading the Qur'an. Students learn to read the Qur'an easily through the sorogan method.